Heavy Metal Adsorption and Release on Polystyrene Particles at Various Salinities - Barus, Beta Susanto; Chen, Kai; Cai, Minggang; Li, Rongmao; Chen, Huorong; Li, Cong; Wang, Jun; Cheng, Sha-Yen (Frontiers in Marine Science, 2021)
Microplastics (MPs) and heavy metals are two major types of pollutants that interact with each other, but they are poorly understood. Polystyrene (PS) is a type of MP that is often detected in aquatic environments. In this study, we examined the adsorption capacity and release rate of heavy metals with respect to different particle sizes of PS, heavy metals, initial heavy metal concentrations, and salinities. Virgin (new) PS with diameters of 20, 50, 130, and 250 µm was used in this study, and four heavy metals (lead, cadmium, copper, and zinc) were used. The results showed that larger PS particle sizes adsorbed more heavy metals even though it took longer to achieve equilibrium adsorption. An increase in heavy metal concentration caused the adsorption capacity (µg/g) of PS particles to also increase, but the adsorption rate (%) decreased. Increased salinity of the heavy metal solution resulted in a slower adsorption time and a lower adsorption capacity and release rate from the surface of PS particles. Different heavy metals also had different adsorption capacities. Pb was consistently more highly adsorbed by MPs, followed by Cu, Zn, and Cd. Larger PS sizes released heavy metals faster than smaller PS sizes, and the amounts of heavy metals released were higher. The heavy metal with the highest release rate was Cd, followed by Pb, Cu, and Zn. Finally, our findings highlight the interactions between PS and heavy metals and strongly support that PS particles can act as vectors for heavy metals in aquatic systems.